2014
DOI: 10.1371/journal.pone.0095228
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Mutations in EGFR, KRAS and TP53 Genes in Human Lung Cancer Tumors Detected by Ion Torrent DNA Sequencing

Abstract: Lung cancer is the most common malignancy and the leading cause of cancer deaths worldwide. While smoking is by far the leading cause of lung cancer, other environmental and genetic factors influence the development and progression of the cancer. Since unique mutations patterns have been observed in individual cancer samples, identification and characterization of the distinctive lung cancer molecular profile is essential for developing more effective, tailored therapies. Until recently, personalized DNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Clinical success with combination targeted therapy depends on the identification of molecular abnormalities for co-administration of a single or combination of target agents against the detected therapeutic targets [41]. In our study, the results indicated that the co-occurrence of mutation (17.8%) or copy number alterations (38.2%) were identified in a significant proportion of tumor samples.…”
Section: Discussionmentioning
confidence: 61%
“…Clinical success with combination targeted therapy depends on the identification of molecular abnormalities for co-administration of a single or combination of target agents against the detected therapeutic targets [41]. In our study, the results indicated that the co-occurrence of mutation (17.8%) or copy number alterations (38.2%) were identified in a significant proportion of tumor samples.…”
Section: Discussionmentioning
confidence: 61%
“…This approach can detect thousands of single-nucleotide variations and rearrangements-and although the same specific single-nucleotide variation mutations (e.g., in EGFR and Kirsten rat sarcoma viral homolog gene [KRAS]) are often found in different patients, identical breakpoints in genetic rearrangements have not been detected among different patients. 87,88 Finally whole-exome or whole-genome sequencing has been proposed, but it suffers from being expensive, not being applicable for rearrangements, being hard to implement in the clinic, and having limited sensitivity as currently available.…”
Section: May 2016mentioning
confidence: 99%
“…22 The additional commonality of many recurrent SNV mutations, such as EGFR and KRAS, means they are often shared even between independent tumors. 23 In contrast, the probability of detecting an identical somatic chromosomal breakpoint in two unrelated tumors is extremely unlikely, if not zero. The common TMPRSS2-ERG fusion is observed in approximately 50% of patients with prostate cancer.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%